(untitled) (Communications in Computational Physics, 2010)
A set of 2D steady state finite element numerical simulations of electromagnetic fields, eddy currents distribution and induction heating pattern has been done for different thicknesses of a metal workpiece. Comparison between the calculation results show the importance of workpiece thickness on induction heating process including electromagnetic field distribution, eddy currents pattern, heating structure and coil efficiency.